(untitled) (Revista Archai, 2021)
In Protagoras’ so called Great Speach, in Plato’s dialogue named after him, the Greek philosopher attributes the sophist a myth about the origin, development and nature of human beings, which has philosophical relevance. It is said that the gods created the mortal beings out of two elements, earth and fire. They assigned two titans, Epimetheus and Prometheus, to provide mortals with their faculties. Do this implies that creation had not been finished by the gods? To what extent do the gods entirely create human beings? Is this mith a creationist one? In this paper, the development of living beings is divided in four stages, and different hermeneutic and explanatory models are proposed to adress the myth and answer the questions raised before.